Who is an African?: race, identity, and destiny in post-apartheid South Africa - Kaunda, Chammah J; Hewitt, Roderick R (Lexington Books/Fortress Academic, 2018)
The subject of race and identity is a burning issue which continues to occupy the attention not only of South Africans but also the wider residents of the continent of Africa and those who are Africans in the Diaspora. The outburst of xenophobic attacks against foreigners mostly of Black African origins in some communities of Kwa-Zulu Natal and areas of Johannesburg during 2008 and 2015 has raised questions about the social cohesion of South African society linked to unresolved structural identity issues bequeathed by the nation’s past colonial and apartheid legacy. This publication argues that there is an embedded schizophrenic identity crisis within the society that requires scholarly interrogation. The chapters assemble scholarly voices from different ethnic groups that examine the central research question of this study: Who is an African? Within the wider Southern African context, identity and ethnicity politics are framing nationalist economic policies and are impacting on social cohesion within many countries. Writing from different social and racial locations the authors have critically engaged with the central question and offer some important insights that can serve as a resource for all nations grappling with issues of race, ethnicity, identity constructed politics, and social cohesion.